Interprofessional Collaboration Between Pharmacists, Nurses, and Healthcare Administrators in Improving Medication Safety and Patient Outcomes (The Review of Diabetic Studies, 2024)
Medication errors and adverse drug events (ADEs) continue to challenge patient safety across healthcare systems, especially in fragmented care settings. Structured interprofessional collaboration involving pharmacists, nurses, and healthcare administrators has been associated with improvements in medication management processes, including prescribing, dispensing, administration, and monitoring. This synthesis examines evidence on how coordinated teamwork among these professionals reduces medication errors and preventable ADEs by enhancing communication, shared decision-making, and systemic oversight. Quantitative analyses reveal that integrated collaboration correlates with reductions in prescribing and administration errors, decreased ADE incidence, shorter hospital stays, and increased incident reporting rates. Qualitative findings highlight the importance of clear role delineation, supportive organizational culture, and adaptable communication frameworks such as ISBAR in sustaining effective collaboration. The tri-professional model leverages complementary expertise to create layered safety checks without inefficiency, with administrative leadership playing a key role in embedding these practices into routine workflows. Ethical considerations emphasize equitable participation, confidentiality, non-punitive reporting environments, and resource allocation fairness. Coordinated pharmacist–nurse–administrator efforts contribute to improved medication safety outcomes and clinical benefits across diverse care settings, demonstrating the value of embedding collaborative structures within healthcare organizations.